IMPLEMENTASI PEMAHAMAN KONSEP SISWA SEKOLAH DASAR MELALUI CTL BERBANTUAN MEDIA VIKAIRAN - Febriani, Tri; Roestika Rini, Zulmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The mathematical conceptual understanding of lower-grade elementary school students remains relatively low due to less contextual learning processes. This study aimed to examine the effect of the Contextual Teaching and Learning (CTL) model assisted by interactive cartoon measurement video media (known as Vikairan) on the conceptual understanding of second-grade elementary school students. This study employed a quantitative approach with a quasi-experimental design, specifically utilizing the non-equivalent control group design. The research sample consisted of second-grade students, with class 2B designated as the experimental group and class 2A as the control group. Data were collected through conceptual understanding test scores. The data analysis revealed a significant difference in conceptual understanding between the two classes (p = 0.018 < 0.05), with the experimental group’s mean score (68.10) being higher than that of the control group (63.70). Meanwhile, the regression analysis indicated that the student response questionnaire scores did not exert a significant influence on their conceptual understanding (p = 0.315 > 0.05). This study concludes that implementing the CTL model assisted by Vikairan interactive cartoon video media is effective in improving the mathematical conceptual understanding of second-grade students. Practically, the collaboration between this contextual model and interactive audiovisual media offers a viable solution for teachers to reduce student boredom and facilitate the visualization of abstract mathematical concepts in lower grades.